The Formation of the Ukrainian Language Prospective Teachers’ Professional Competence in Classes of Linguodidactics (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The paper presents academic experience of the formation of philologists’ language and speech competences in classes of the Ukrainian language teaching methods.
Keywords: competence; speech communication; linguodidactics; forms and methods of classes organization